1991
DOI: 10.1002/macp.1991.021921207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkyl groups on the rate constants of propagation and termination in the radical polymerization of dialkyl itaconates

Abstract: Polymerization of dialkyl itaconates with dimethyl azoisobutyrate (5) was studied in benzene at 50 "C by means of electron spin resonance (ESR). The monomers used are dimethyl (l), diethyl (2), dibutyl (3) and di-2-ethylhexyl (4) itaconates. All the polymerization systems involve ESRobservable propagating polymer radicals under the actual polymerization conditions. The polymerization rate (R,) and degree of polymerization of the resulting polymer increase in going from shorter to longer alkyl groups. The ESR-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 5 publications
3
28
0
Order By: Relevance
“…Conversions were low and increased with the length of the alkyl chain (Table 3). These results are in accord with those shown by Sato et al [24] in conventional free radical polymerization for a homologous series of methacrylic acid monoesters. These authors also found that the rate of polymerization increased with the size of the alkyl substituent.…”
Section: S the Growing Chain Radicalsupporting
confidence: 93%
“…Conversions were low and increased with the length of the alkyl chain (Table 3). These results are in accord with those shown by Sato et al [24] in conventional free radical polymerization for a homologous series of methacrylic acid monoesters. These authors also found that the rate of polymerization increased with the size of the alkyl substituent.…”
Section: S the Growing Chain Radicalsupporting
confidence: 93%
“…[14,65] In the case of dialkyl itaconates, EPR and PLP-SEC results were not always in quantitative agreement, although both methods revealed that the k p values are at least one order of magnitude lower than for styrene and MMA. [22,23,63,64,66,67] Significant discrepancies in k p values for benzyl methacrylate and butyl methacrylate obtained by the two methods have been observed. [9,10,43,44] It has been suggested that the k p values of acrylic esters determined by the EPR method [39][40][41] and PLP-SEC [12] are in poor agreement because of the presence of mid-chain radicals, which influences the measurements to different extents.…”
Section: à3mentioning
confidence: 77%
“…[31] More recently, the EPR method has been applied to further studies of the polymerizations of styrene, [37,38] acrylates, [39][40][41] methacrylates, [42][43][44][45][46][47] acryland methacrylamides, [48][49][50][51] a-substituted acrylates, [52,53] itaconate and related monomers, [54][55][56][57][58] as well as nonconjugated monomers. [59][60][61] Determination of k p by the EPR method and PLP-SEC has resulted in good agreement for styrene, [7,37] methyl methacrylate, [8,42] dodecyl methacrylate, [43,62] dimethyl itaconate, [22,63,64] and methyl a-(2-carbomethoxyethyl)…”
Section: à3mentioning
confidence: 96%
“…[9][10][11][12][13] In previous articles, Some Lewis acids are well-known to influence radical polymerizations of acrylic monomers such as we studied the effect of SnCl 4 on the homo-and methyl methacrylate, methyl acrylate, and acrylocopolymerization behaviors of diethyl itaconate by nitrile, where acceleration of polymerization and means of ESR. 4,7 increase in molecular weight of the resulting polyOn the other hand, much attention has been paid mers are observed.…”
Section: Introductionmentioning
confidence: 99%